2014
DOI: 10.1182/blood-2013-10-534297
|View full text |Cite
|
Sign up to set email alerts
|

The addition of sirolimus to tacrolimus/methotrexate GVHD prophylaxis in children with ALL: a phase 3 Children’s Oncology Group/Pediatric Blood and Marrow Transplant Consortium trial

Abstract: • Adding sirolimus to tacrolimus/methotrexate GVHD prophylaxis decreased grade 2-4 aGVHD but did not improve survival in pediatric ALL.• The addition of sirolimus to tacrolimus/methotrexate increased rates of VOD and TMA compared with tacrolimus/methotrexate alone.Sirolimus has activity against acute lymphoblastic leukemia (ALL) in xenograft models and efficacy in preventing acute graft-versus-host disease (aGVHD). We tested whether addition of sirolimus to GVHD prophylaxis of children with ALL would decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 39 publications
4
121
0
3
Order By: Relevance
“…28 More recently, in randomized trials, the addition of sirolimus to tacrolimus or as a substitute for methotrexate has been shown to reduce acute GvHD without affecting overall survival. [29][30][31] To our knowledge, the current study is the first phase II randomized trial to investigate the efficacy of sirolimus as acute GvHD prophylaxis in truly non-myeloablative HCT. However, there has been some experience in the reduced-intensity conditioning setting, and there has been a recent preliminary abstract report from a randomized phase III trial comparing tacrolimus, methotrexate and sirolimus to conventional sirolimus-free regimens.…”
Section: Cumulative Incidence (%) Hr (95% Ci); Pmentioning
confidence: 99%
“…28 More recently, in randomized trials, the addition of sirolimus to tacrolimus or as a substitute for methotrexate has been shown to reduce acute GvHD without affecting overall survival. [29][30][31] To our knowledge, the current study is the first phase II randomized trial to investigate the efficacy of sirolimus as acute GvHD prophylaxis in truly non-myeloablative HCT. However, there has been some experience in the reduced-intensity conditioning setting, and there has been a recent preliminary abstract report from a randomized phase III trial comparing tacrolimus, methotrexate and sirolimus to conventional sirolimus-free regimens.…”
Section: Cumulative Incidence (%) Hr (95% Ci); Pmentioning
confidence: 99%
“…7,8,13,14 In the first prospective study of TMA in pediatric patients, incidence was reported to be as high as 35% and presence of TMA associated with higher non-relapse mortality than in patients without TMA. 1 Jodele et al 15 proposed that TMA is characterized by multi-organ endothelial injury affecting kidneys, gut, serosal surfaces, heart, skin and lungs, all in the setting of hemolytic anemia and thrombocytopenia.…”
mentioning
confidence: 99%
“…Име-ются данные об использовании сиролимуса для лече-ния реакции «трансплантат против хозяина» (РТПХ) у больных, получивших ТГСК. Результаты исследова-ния у детей показали, что сиролимус снизил частоту развития острой РТПХ, но показатели выживаемости не улучшились [33].…”
Section: перспективы оптимизации лечения острого мие-лобластного лейкозаunclassified